Multifaceted applications of green carbon dots synthesized from renewable sources - Tejwan, Neeraj; Saha, Subbroto Kumar; Das, Joydeep (Advances in colloid and interface science, 2020)
Fluorescent carbon dots (CDs) are an emerging class of nanomaterials in the carbon family. There are various inexpensive and renewable resources that can be used to synthesize green CDs, which have received immense attention from researchers because of their improved aqueous solubility, high biocompatibility, and eco-friendly nature compared with chemically derived CDs. Additional surface passivation is not required, as heteroatoms are present on the surface of green CDs in the form of amine, hydroxyl, carboxyl, or thiol functional groups, which can improve their physicochemical properties, quantum yield, and the probability of visible light absorption. Green CDs have potential applications in the fields of bioimaging, drug/gene delivery systems, catalysis, and sensing. Since their discovery, there have been several review articles that describe the synthesis of green CDs and some of their applications. However, there are no review articles describing the synthesis and complete applications of green CDs. Here, we provide detailed information regarding their synthesis and applications based on the available literature. In addition, we discuss some of the less explored applications of green CDs and the challenges that remain to be overcome. [Display omitted] •Carbon dots (CDs) are the new fellow of carbon family having a size less than 10 nm.•Green CDs possess unique features, like facile synthesis, outstanding photoluminescence, and higher biocompatibility.•Green CDs have been extensively used in biological applications, like bioimaging, drug-gene delivery system and biosensing.•Green CDs have also been applied in the field of chemistry, like photocatalytic reactions and chemical sensing.•This review summarized the progress of research on green CDs regarding its synthesis, applications, and the challenges.